Upper Miocene planktonic foraminifera from Algarve. Chronostratigraphical implications - Legoinha, P. (Ciências da Terra, 2003)
Ciências da Terra(UNL) Nº 15, pp. 199-208 New data on the planktonic foraminifera from the Upper Miocene Cacela Formation and Mem Moniz spongoliths are presented. The coiling type of Globorotalia menardii from Cacela and Quelfes and the occurrence at Quelfes of G. miotumida allow correlation with the bio-events 1 to 3 (7,512 to 7,24 Ma; Sierro et al., 1993; 2001) that have been recognized in the Guadalquivir Basin (Spain). The presence of Neogloboquadrina acostaensis and N. humerosa at Mem Moniz points out to the Upper Miocene (Tortonian, upper N16, or even N17). Mem Moniz spongoliths are correlated with the Cacela Formation. Some S7Srf86Sr isotopic ages ofmollusc or foraminifera shells don't fit well with finer biostratigraphic record and present wide error margins.